Inhibition of Myostatin Reduces Collagen Deposition in a Mouse Model of Oculopharyngeal Muscular Dystrophy (OPMD) With Established Disease - Harish, Pradeep; Forrest, Leysa; Herath, Shanti; Dickson, George; Malerba, Alberto; Popplewell, Linda (Frontiers in Physiology, 2020)
Background Oculopharyngeal muscular dystrophy (OPMD) is a late-onset muscle disease presented by ptosis, dysphagia, and limb weakness. Affected muscles display increased fibrosis and atrophy, with characteristic inclusion bodies in the nucleus. Myostatin is a negative regulator of muscle mass, and inhibition of myostatin has been demonstrated to improve symptoms in models of muscular dystrophy. Methods We systemically administered a monoclonal antibody to block myostatin in the A17 mouse model of OPMD at 42 weeks of age. The mice were administered a weekly dose of 10 mg/kg RK35 intraperitonially for 10 weeks, following which serum and histological analyses were performed on muscle samples. Results The administration of the antibody resulted in a significant decrease in serum myostatin and collagen deposition in muscles. However, minimal effects on body mass, muscle mass and myofiber diameter, or the density of intranuclear inclusions (INIs) (a hallmark of disease progression of OPMD) were observed. Conclusion This study demonstrates that inhibition of myostatin does not revert muscle atrophy in a mouse model with established OPMD disease, but is effective at reducing observed histological markers of fibrosis in the treated muscles.